2023
DOI: 10.3389/fnut.2023.979380
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported ongoing adherence to diet is associated with lower depression, fatigue, and disability, in people with multiple sclerosis

Abstract: IntroductionIncreasingly, dietary improvements have been shown to have positive associations with health outcomes in people with multiple sclerosis (pwMS). However, adhering to a MS-specific or high-quality diet may be a challenge. We therefore assessed the level of diet-adherence necessary to improve health outcomes of depression, fatigue, and disability.MethodsData from an international population of pwMS followed over 7.5 years (n = 671) were analyzed. Self-reported diet quality via diet habits questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In MS, dietary intervention can lead to a reduction in neurological fatigue, disability scores (Katz Sand et al, 2019;Ovcharova et al, 2022), as well as depression (Yu et al, 2023). Different studies reported that Mediterranean diet adherence was Influence of obesity on neurodegenerative diseases.…”
Section: Diet and Exercise As Rescuing Interventionmentioning
confidence: 99%
“…In MS, dietary intervention can lead to a reduction in neurological fatigue, disability scores (Katz Sand et al, 2019;Ovcharova et al, 2022), as well as depression (Yu et al, 2023). Different studies reported that Mediterranean diet adherence was Influence of obesity on neurodegenerative diseases.…”
Section: Diet and Exercise As Rescuing Interventionmentioning
confidence: 99%
“… 1 , 2 There are limited prospective trials investigating the efficacy of three commonly recommended diets, the Swank, overcoming MS (OMS), and Wahls diets. 3 6 Dairy and gluten are two components for which the recommendations vary between these diets; the Wahls diet restricts both dairy and gluten intake, whereas the Swank and OMS diets restrict dairy but not gluten. These dietary exclusions were initially recommended based on studies that suggested a correlation between cow's milk consumption and MS prevalence as well as a correlation between coeliac disease and MS prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an autoimmune disease that leads to a gradual damage and loss of the myelin sheath of neurons in the spinal cord, brain and optic nerve ( 1 ). These injuries then lead to atrophy of the affected nerves over time.…”
Section: Introductionmentioning
confidence: 99%
“…These injuries then lead to atrophy of the affected nerves over time. The atrophy that occurs at the onset of the disease is mild but progresses over time, eventually leading to numerous disabilities in these patients ( 1 ). Among the Middle Eastern countries, Iran has the highest prevalence rate of MS ( 2 ).…”
Section: Introductionmentioning
confidence: 99%